Regio‐Selective Phosphation and Phosphonation of 9‐Fluorenones. Issue 18 (15th November 2016) - Deshidi, Ramesh; Devari, Shekaraiah; Rizvi, Masood; Shah, Bhahwal Ali
Abstract: A method for regio‐selective phosphation and phopshonation at 9‐position of fluorenones has been developed. The outcome of reaction can be controlled by varying temperature viz., at low temperature phosphonate is the exclusive product, whereas at high temperature phosphate is the favoured product. The reaction is easy to set up, involves mild conditions and proceeds efficiently over a broad range of substrates with excellent functional group tolerance. Abstract : A facile method for regio‐selective phosphation and phopshonation at carbonyl moiety of 9‐fluorenones by tuning temperatures has been developed. The strategy brings to fore the migratory aptitude of phosphonates in cyclopentadienyl systems, wherein it is implied that such systems obviate the use of strong bases usually required in the absence of an activating group at α ‐position. Additionally, easy setup, mild conditions, broad substrate scope and excellent functional group tolerance are some of the advantages.